The Role of Sound Design in Generating Conflict and Tension in World War Z (2013) - Cikka Rahma; Irman Nurhapitudin; Yoga Sudarisman (Journal of Educational Studies, 2026)
This study examines how sound design contributes to the construction of conflict and tension in World War Z (2013). Rather than functioning merely as an accompanying cinematic element, sound design serves as a narrative mechanism that shapes audience perception, emotional engagement, and spatial awareness throughout the film. This research employed a descriptive qualitative approach using textual film analysis. Twenty scenes were purposively selected based on the presence of dominant sound design elements including voice, music, sound effects, silence, and spatial sound and their direct contribution to the development of narrative conflict and tension. The analysis was conducted through thematic coding and interpreted using film sound theories proposed by Bordwell et al. (2019) and Petrie and Boggs (2018). The findings reveal four principal narrative functions of sound design. First, auditory cues trigger narrative disruption by prompting audiences to anticipate conflict before it becomes visually apparent. Second, dense and overlapping sound layers represent the collapse of social order while increasing emotional intensity and narrative immersion during outbreak sequences. Third, deliberate silence generates psychological tension by directing audience attention toward uncertainty and anticipation. Fourth, spatial sound constructs invisible threats through off-screen and directional audio, encouraging viewers to perceive danger beyond the visual frame and strengthening suspense. Collectively, these auditory strategies influence audience cognition, emotional responses, and engagement with the film's narrative progression. This study concludes that sound design in World War Z (2013) acts as a storytelling system that systematically constructs conflict, tension, and cinematic experience rather than functioning solely as a technical or aesthetic feature. The findings contribute to film studies by demonstrating the narrative significance of sound design and by integrating film sound theory with literary narrative analysis. In addition, the study offers practical insights for filmmakers, sound designers, and future researchers seeking to understand how auditory elements can enhance cinematic storytelling and audience immersion.